Mechanistic bases of the exaggerated mechanoreflex in peripheral artery disease - Rollins, Korynne Sierra (Kansas State University, 2021)
Mechanically-activated (MA) channels located on group III and IV skeletal muscle afferents stimulated during contraction elicit necessary autonomic and cardiovascular adjustments to exercise. However, in peripheral artery disease (PAD) MA channels become chronically sensitized and contribute to exaggerated mechanoreflex activation. Exaggerated mechanoreflex activation results in aberrant increases in sympathetic nervous system activity, heart rate, and blood pressure during exercise. This is of clinical importance because acute exaggerated autonomic and cardiovascular responses during exercise increase the patient’s risk of suffering from an adverse cardiovascular event. Products of cyclooxygenase enzyme activity have been shown to chronically sensitize the mechanoreflex in PAD but the identity of the muscle afferent receptors that mediated the sensitization remained unclear. In this sequence of experiments presented in my dissertation, we use a rat model of simulated PAD in which the femoral artery is chronically ~72 hrs ligated which mimics the blood flow patterns and the exaggerated blood pressure response during exercise in PAD patients. To gain insights into exaggerated mechanoreflex activation, we use a 1 Hz repetitive/dynamic hindlimb skeletal muscle stretch (a model of mechanoreflex activation isolated from contraction-induced metabolite production) and dynamic hindlimb skeletal muscle contraction to explore downstream intracellular signaling pathways and structural elements associated with MA channel gating within sensory neurons. In the studies presented below, we find that both biochemical and biophysical properties of sensory neurons contribute to MA channel sensitivity and the exaggerated mechanoreflex in PAD. In the first study (Ch. 2) we found that thromboxane A2 (TxA₂) receptor blockade reduced the mechanoreflex in rats with ligated femoral arteries. TxA₂ receptors are coupled to G[subfield q] proteins that when stimulated active phospholipase C which cleaves phosphatidylinositol 4,5-bisphosphate to form diacylglycerol and inositol-1,4,5 trisphosphate (IP₃). IP₃ stimulates its receptor on the endoplasmic reticulum to cause calcium release into the cytosol. Elevated cytosolic calcium has been shown to sensitize MA piezo channels, the channel thought to underlie mechanoreflex activation. In the second study (Ch. 3) we found the IP₃ receptor blockade reduced the mechanoreflex in rats with ligated femoral arteries. Intracellular signaling can alter structural components of the cell including the cytoskeleton. Actin is one of the three major components of the cytoskeleton and during inflammatory conditions, there is increased actin polymerization (i.e., more F-actin production). Increased F-actin causes a change in static plasma membrane tension which increases the sensitivity of MA piezo channels. In the third study (Ch. 4) we found that actin polymerization inhibition reduced the exaggerated mechanoreflex in rats with ligated femoral arteries. The culmination of these studies provides evidence of biochemical and biophysical components of MA channel modulation that result in chronic sensitization and an exaggerated mechanoreflex in a rat model of simulated PAD.
Keywords: Sensory neuron; Exercise pressor reflex; Blood pressure